2004
DOI: 10.1097/00004728-200407000-00021
|View full text |Cite
|
Sign up to set email alerts
|

The Fat Pad Sign Following Elbow Trauma in Adults

Abstract: Our data using MR imaging suggests that fat pad elevation in the presence of recent trauma is frequently associated with a fracture. The size of the effusion, anterior/posterior fat pad elevation, or a combination of both does not correspond to the likelihood of an underlying fracture. MR imaging reveals a broad spectrum of bone and soft tissue injury beyond that recognizable on plain radiographs as demonstrated by all patients in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Studies have shown that 2-10% of proximal femur fractures may be missed on initial radiographs, especially in the trauma setting [5,6]. Unlike other joints, where the presence of an effusion on plain radiograph of the ankle [7] or a displacement of the posterior fat pad in the elbow is informative [8,9], there has yet to be a reliable radiographic sign at the hip to indicate an occult hip fracture. Occult proximal femur fractures can lead to devastating consequences, complicating surgical intervention and comprising ideal outcomes [10].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 2-10% of proximal femur fractures may be missed on initial radiographs, especially in the trauma setting [5,6]. Unlike other joints, where the presence of an effusion on plain radiograph of the ankle [7] or a displacement of the posterior fat pad in the elbow is informative [8,9], there has yet to be a reliable radiographic sign at the hip to indicate an occult hip fracture. Occult proximal femur fractures can lead to devastating consequences, complicating surgical intervention and comprising ideal outcomes [10].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed this fat pad sign on radiographs, especially in cases of elbow trauma (Figure 4). If the first plain radiograph does not show a fracture, indirect signs of fracture should be looked for (17,18). However, a visible anterior fat pad might be normal if it is close to the bone (17).…”
Section: Discussionmentioning
confidence: 99%
“…The term “occult fracture” is defined broadly as a radiographically undetectable or subtle abnormality that has been missed on initial radiographs ( 4 ). The abnormalities which can indicate possible fractures include the fat pad sign because of joint effusion, immobility, stable pressure pain point, and abnormal swelling ( 17 , 18 ). We have not found any previous study that has attempted to determine the prevalence of occult fractures and their clinical significance in children with radiograph-negative AEI and clinical suspicion of fracture.…”
Section: Discussionmentioning
confidence: 99%